Sejarah masyarakat Bugis di Kedah: 1668-1847 - Jasni, Ahmad (2021)
This study looks into the arrival of the Bugis to Kedah between 1668 – 1847. Writings about the Bugis in Kedah have received little attention even though this ethnic was involved in marriage with the Royal family and interference in Kedahan politics. Therefore, this study intend to study the factors that contribute to the arrival of the Bugis to Kedah, identify their interference in Kedahan politics in the 17th to 19th century and study their Bugis legacy in socio-cultural aspects in Kedah today. This Historical Methodology to achieve the objectives of the study used literature references, analysing primary and secondary resources. Other than that, the study’s instruments included interviews with respondents who are Bugis descendents in Kedah, Patron and Committee Members of the Kedah Historical Society as well as academicians involved in a forum on the location of Daeng Parani’s tomb. Findings showed that there were seven factors contributing to the arrival of the Bugis to Kedah, all of which were based on Siri’ and Pesse philosophy as well as the Three-Point concept. Agitation within the Kedah palace gave opportunity for Bugis interference to the extend that a Bugis descendent was once elected to be the Crown Prince of Kedah in 1847. The socio-cultural legacy of the Bugis in Kedah is less found because it has long separated from their original culture. In conclusion, the study has contributed and provided significant value to many parties including Bugis in Kedah as well as the general public. The artifacts found were used as exhibition material to preserve the historical effects of Bugis in Kedah